Novel techniques for efficient PAPR reduction in NOMA systems for future wireless networks - Inam Abousaber; Amira A. Mohamed; Haitham F. Abdallah (Journal of Information and Telecommunication)
Fifth-generation (5G) networks are designed to overcome critical challenges, including achieving high data rates, supporting massive device connectivity, and ensuring low latency. Non-Orthogonal Multiple Access (NOMA) significantly enhances spectral efficiency and network capacity within this framework. NOMA has a problem with a high Peak-to-Average Power Ratio (PAPR). This creates nonlinear distortion, reduces power amplifier efficiency, and increases out-of-band radiation, making it less useful in 5G and B5G networks. To address this, two PAPR reduction methods are proposed: Improved Salp Swarm Algorithm-based Partial Transmit Sequence (PTS-ISSA) and Iterative Sub-block Phase Rotation (ISPR). PTS-ISSA minimizes PAPR by phase rotation of sub-blocks, offering the best reduction but at higher computational complexity, making it ideal for systems with abundant resources. ISPR, on the other hand, employs iterative phase rotation without side information, balancing performance with lower complexity, making it suitable for resource-constrained applications. Evaluated under Rician fading and AWGN channels, both methods outperform traditional techniques in PAPR reduction and Bit Error Rate (BER) performance. While PTS-ISSA is optimal for high-performance systems, ISPR serves lightweight, real-time applications. These methodologies show potential for the next-generation wireless networks, supporting scenarios from IoT to ultra-reliable low-latency communications by optimizing the trade-off between performance and complexity.